A Chemical Overview of Azanza garckeana - Yilni Edward Bioltif; Naanma Bioltif Edward; Terry Dalyop Tyeng (Biology, Medicine, & Natural Product Chemistry, 2020)
Azanza garckeana is a popular fruit tree in Nigeria, specifically in Gombe State, where it is locally called ‘goron tula’ which means ‘Kola of Tula’. It is also found in part of some African countries. Different plant part of this small tree/shrub has recorded different uses by the locals; uses ranging from its fruits being edible and others parts helping to remedy different diseases, especially sexually related diseases. It also records use as booster for sexual performance. The uses of the plant are majorly attributed to the presence of chemicals. Its local use initiates the necessity of this review to enhance the research for drug discovery since Chemicals are the chief constituencies responsible for its medicinal importance.